Combination of the underutilised legumes Canavalia ensiformis (L.) D.C. and Canavalia ensiformis (L.) D.C. with sorghum: integrated assessment of their potential as conserved ruminant feed - Lima-Orozco, R.; Van Daele, I.; Álvarez-Hernández, U.; Fievez, V. (Cuban Journal of Agricultural Science, 2016)
The present research studied the integrated assessment of the potential as conserved ruminant feed of combined sorghum-Jack bean or Velvet bean.Data of whole plant sorghum silage supplemented with dry beans of Jack beans (JB) and whole plant sorghum-Jack beans silage or whole plant sorghum-Velvetbean (VB) silage from Lima-Orozco et al. (2014) were used to assess the integration of agronomic considerations in an overall evaluation including biomass production, nutritive value and conservation quality. The metabolisable energy (ME) content of the combined sorghum-JB silages was 1.26 times greater than the ME content of pure sorghum silage supplemented with dry beansfrom JB. Additionally a greater amount of protein digestible in the small intestine (dCPSI) was observed (62.9 vs 43.5 g/kg DM). It was concluded that the ME content and dCPSI of the sorghum- JB silages are 1.26 or 1.44 times higher than sorghum-JB silage or for pure sorghum silage supplemented with dry beans fromJB. Moreover, a much larger surface is required for the sorghum silage and dry JB alternative. Hence, combined sorghum-JBsilage seemed the best alternative studied here in terms of DM yield, dCPSI and ME supply.Key words: sorghun, seasonal legumes, silage